Model of an intelligent and automated negotiation agent for the service level agreement negotiation process in cloud computing - Muhamad Hariz Muhamad Adnan (Tanjung Malim, 2023)
Model of an intelligent and automated negotiation agent for the service level agreement negotiation process in cloud computing by Muhamad Hariz Muhamad Adnan